Optimization of SWAT-Paddy for modeling hydrology and diffuse pollution of large rice paddy fields. (August 2020) - Ouyang, Wei; Wei, Peng; Gao, Xiang; Srinivasan, R.; Yen, Haw; Xie, Xianhong; Liu, Lianhua; Liu, Hongbin
Abstract: The Soil and Water Assessment Tool (SWAT) simplified the hydrological processes in large patches of paddy fields. Based on the original SWAT code, the main equations are modified and validated with the long-term field observations in freezing-thawing watershed. The original SWAT and SWAT with paddy module (SWAT-P) both perform well in the simulation of stream flow at the basin scale (NSE ≥ 0.7). SWAT-P performs better in the soil water simulation (RMSE = 24.22 mm, smaller than 104.63 mm of SWAT). The monthly diffuse nitrogen loadings simulated by SWAT-P are within a reasonable range and close to the monitored nitrate loads in 2011 and 2012. SWAT-P represents the ponding water depth dynamics during the rice growing period. The original SWAT overestimates the diffuse pollution loads in the freeze-thaw period. SWAT-P has better performance for water cycles and diffuse pollution load simulations in watersheds with large rice paddy fields. Highlights: The original SWAT and SWAT-P both performed well in the simulation of stream flow at the basin scale. The SWAT-P performed better in the soil water simulation at HRU scale. The monthly diffuse TN simulated by the SWAT-P were within a reasonable range and close to monitored values. SWAT-P still underestimated the diffuse N load compared to observed data, but better than original SWAT during the spring.